2019
DOI: 10.1016/j.ijcard.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Medical therapy for atherosclerotic cardiovascular disease in patients with myocardial injury after non-cardiac surgery

Abstract: Background: Myocardial injury after non-cardiac surgery (MINS) is a common postoperative cardiovascular complication and is associated with short and long-term mortality. The objective of the study was to describe the contemporary management of patients with and without MINS after total joint and spine orthopedic surgery at a large tertiary care hospital. Methods: Adults admitted for total joint and major spine surgery from January 2013 through December 2015 with ≥1 cardiac troponin (cTn) measurement during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“… 22 Based on these findings, 22 it is reasonable to assume that patients may benefit from basic cardiac medication for the secondary prevention of MI after noncardiac surgery. However, the current results, consistent with a previous study, 29 showed that in clinical practice the proportion of patients with perioperative MI prescribed basic cardiac medical therapy remained low.…”
Section: Discussionsupporting
confidence: 92%
“… 22 Based on these findings, 22 it is reasonable to assume that patients may benefit from basic cardiac medication for the secondary prevention of MI after noncardiac surgery. However, the current results, consistent with a previous study, 29 showed that in clinical practice the proportion of patients with perioperative MI prescribed basic cardiac medical therapy remained low.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, many patients with vascular disease or MINS do not receive medicines for secondary prevention. 10,97…”
Section: Postoperative Surveillancementioning
confidence: 99%
“…Currently, many patients with vascular disease or MINS do not receive medicines for secondary prevention. 10,97 Current Canadian Society of Cardiology 2017 guidelines provide a strong recommendation for daily postoperative cTn measurements for 48 to 72 hours after noncardiac surgery in elevated-risk patients based on moderate-quality evidence. 7 These guidelines identify elevated-risk patients as those with elevated preoperative BNP measurements, Revised Cardiac Risk Index score ≥1, age ≥65 years, or age of 45 to 64 years with significant cardiovascular disease.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…While initiation of common therapies that are likely beneficial for MINS seem like simple strategies, one retrospective study found that only 48% of patients diagnosed with MINS were discharged on a combination of aspirin and statin. 17 The current AHA statement did not go as far as recommending the postoperative specialist order invasive or noninvasive ischemic coronary testing for patients diagnosed with postoperative MINS, but do encourage cardiovascular consultation in order to determine these individualized needs. One retrospective study of more than 1000 patients who had invasive coronary angiography for postoperative MINS found that only 54% had non-flow-limiting coronary stenosis and only 26% required intervention.…”
Section: Role Of the Postoperative Specialistmentioning
confidence: 99%